Creativity of Fiqih Teachers in Improving Student Learning Atmosphere During Pandemic at MTs Rhoudotun Hasanah Tanjung Jabung Timur - Nisak, Sayida Khoiratun; Dewi, Hasna; Munip, Al; Muharramah, Delvia; Wargo, Wargo (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This study aims to determine the creativity of fiqih teachers to improve students' learning atmosphere in the cognitive, affective, and psychomotor domains during Covid-19 pandemic. This research uses a qualitative approach using snowball sampling technique. Data collection techniques were carried out using observation, interview and documentation techniques. The results of this study indicate that the innovations made in improving cognitive, affective and psychomotor abilities include: Teachers apply the quiz game of throwing paper balls to create a fun atmosphere, Teachers also take a scientific approach, provide motivation, good role models for students and hold routine religious activities. Factors that support teacher innovation are internal factors of teacher awareness while external factors of teacher educational background and school contributions. Although limited facilities hinder the innovation process, the school tries to plan the budget for the procurement of the fiqih facilities through the school operational assistance fund gradually.